The Urgence of Siti Bariyah's Thinking in Islamic Education 5.0 - Anjas Pratiwi; M. Solikul Hadi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Siti Bariyah is one of the female figures who has many roles in the development of Muhammadiyah and helped the process of forming a women's organization under the auspices of Muhammadiyah, namely 'Aisyiyah. Siti Bariyah's thoughts can be seen from her contribution to Muhammadiyah, especially in the world of education. This study uses a biographical and social approach. The concept used in this research is the concept of gait. The concept used in this research is the concept of social role theory proposed by Erving Goffman. The method used in this research is the historical method. The historical method used in this research consists of four stages, namely; heuristics, verification, interpretation, and historiography. Siti Bariyah was born in Kauman Village, Yogyakarta on 1325 H/1906 AD and died around 1931 AD. She was active in the Sapa Trisno, Wal Ashri¸ and Maghribi School associations which became the embryo of the 'Aisyiyah movement. He is known to have a high intellect. Siti Bariyah's intellectuality made her have many roles in 'Aisyiyah, especially in the fields of religion, social, and education. Her role in the social field was to help pioneer the Suara 'Aisyiyah magazine, to co-found the Female Student Praja, and to initiate the formation of a federation of women's organizations. His role in the field of education is to participate in initiating the establishment of a kindergarten called Frobelschool and participate in eradicating illiteracy. Eradication of letters in the current era can be interpreted as eradicating language illiteracy, namely English and Arabic. The formation of kindergarten as a cadre of intellectual scholars in the face of the era of disruption. Keywords: Urgency, Siti Bariyah, Islamic Education